Analysis of chemical dependence among adolescents: A review - Ervatti , Aline Cicilioti; Paschoa, Barbara Gomes do Carmo; Benedito, Cecília da Silva; de Castro, Edielson Maria Nabiça; Albani, Karina Costa; Albani, Marcelo Costa; Almança, Rebeca Agnes de Oliveira; de Matos, Maria de Lourdes Ferreira Medeiros; de Matos, Alcemar Antonio Lopes; Norberg, Antonio Neres (Seven Editora, 2023)
The World Health Organization defines adolescence as the period of life that comprises the interval between 10 and 19 years. This is considered a critical phase, of intense changes that go through the physical, emotional and social development. External influences can lead to worrying risk behaviors that often contribute to increased alcohol and drug consumption in this age group. Curiosity and the search for ways to deal with problems are other reasons that lead some adolescents to try these substances. In this context, chemical dependence among adolescents is a public health issue that is perpetuated over different generations, unfolding with different temporal characteristics, causing significant damage, including family disagreements, accidents, involvement with criminal actions, and medical emergencies such as overdose. To face the problem, it is necessary to unravel its roots, understand and look for the warning signs and work on prevention. The treatment requires an efficient multidisciplinary approach and as early as possible, being necessary the understanding and humanitarian reception of the adolescent, encouraging him to regain control over his life and his future, guaranteeing for these individual promising possibilities.DOI:https://doi.org/10.56238/globalhealthprespesc-055